Cost Comparison of Outpatient Versus Inpatient Unicompartmental Knee Arthroplasty. Issue 3 (14th March 2017) - Richter, Dustin L.; Diduch, David R.
Background: Outpatient unicompartmental knee arthroplasty (UKA) has been shown to be safe and feasible when compared with inpatient surgery; however, no studies have evaluated the cost-effectiveness and cost-benefit of performing outpatient versus inpatient UKA. Hypothesis: Significant cost savings can be achieved by transitioning UKAs from an inpatient to an outpatient procedure in an outpatient surgical facility, with no appreciable difference in complication or readmission rates. Study Design: Economic and decision analysis; Level of evidence, 3. Methods: A retrospective chart review of 25 consecutive medial UKAs was performed. A total of 10 inpatient UKAs with a mean length of stay of 1.6 days (range, 1-4 days) and 12 outpatient UKAs were included in the final analysis. A simple difference in costs incurred, reimbursements, and percentage difference between inpatient and outpatient surgery in an outpatient surgical facility was calculated. Charges were subdivided into surgical facility fees, inpatient room charges, operating room supply fees, and other fees. Secondary outcome measures included reason for greater than 1 day stay for the inpatient UKAs, complications, readmissions, and the type of regional anesthesia utilized. Results: The outpatient UKA charges were a mean 20, 500 less per patient than the inpatient average charge of 46, 845. The primary cost savings were attributed to the outpatient surgical facility fee, which averaged 3800 per patient, while the inpatient facility charge was 350% more expensive at 13, 200 per patient (approximately 9500 savings). On the inpatient side, the average reimbursement was 55% of charges, or 25, 550. For outpatient procedures, the average reimbursement was 47%, or 12, 370. There was no difference between the inpatient and outpatient groups in terms of complications or readmissions. Conclusion: This work demonstrated that significant cost savings of roughly 50% can be achieved with an outpatient UKA protocol done at an outpatient surgical facility. Not only is it feasible and economically attractive to perform outpatient UKA, but it can reduce inpatient bed occupancy and resource allocation for a busy hospital.